The Complete Mitochondrial Genome and Phylogenetic Analysis of Rhagastis binoculata (Matsumura, 1909) (Lepidoptera: Sphingidae) - Kuo, Yu-Yun; Chang, Ju-Chun; Li, Yi-Hsuan; Huang, Yu-Feng; Wu, Tzong-Yuan; Nai, Yu-Shin (Genes, 2024)
The mitochondrial genome (mitogenome) Rhagastis binoculata (Matsumura, 1909), an endemic moth species in Taiwan, was sequenced and analyzed. The complete circular mitogenome of R. binoculata is 15,303 bp and contains 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and an AT-rich control region. The mitogenome has an overall nucleotide composition of 41.2% A, 11.9% C, 7.5% G, and 39.4% T, with an AT content of 80.6%. Of the protein-coding genes (PCGs), 12 start with ATG, ATT, and ATC, and COX1 starts with a “CGA” codon. All of the stop codons are “TAA, TAG, or T”. Our phylogenetic analysis of 21 species of Sphingidae insects suggests that R. binoculata is clustered with Rhagastis mongoliana, which belongs to the subfamily Macroglossinae.